The hospitality industry in France within the context of modern features of world tourism development - Hanna Kucheriava; Tatiana Polishchuk (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The article examines the hospitality industry in France as one of the important components of the country's economy. France remains a leader in world tourism and one of the most visited countries in the world. This demonstrates its tourist attractiveness and high competitiveness in the world market of tourist services. Analysing overnight stays in France during the global pandemic, it was found that the number of international tourists in the country has decreased, especially in Paris and the Île-de-France region. Tourist activity in France was practically absent from mid-March to May 2020 due to a number of forced restrictive measures that were in-troduced in the country to prevent the spread of COVID-19. However, due to state support and active promotion of domestic tourism, tourism development indicators were, overall, better than in neighbouring European countries. It was found that the majority of domestic tourists preferred outdoor activities, rural tourism, recreation on the coast. The article analyses the number of overnight stays in hotels in France, it is found that during the summer season of 2020, on average, the overnight stays decreased by 58% compared to the same period in 2019. The number of non-resident tourists decreased by 81%, partially due to the absence of tourists from countries such North America, the Middle East and Asia, which in the pre-crisis period, played a significant role in non-resident tourist influx in France. Furthermore, it was revealed that there are regional differences in the number of overnight stays in hotels. Overall, France's coastal regions have a smaller decrease in tourist numbers than other parts of the country. It is considered that the prospects for the development of the hospitality industry in France, primarily the hotel sector, associated with the adoption of the modern technologies in the hotel enterprises’ activities. Such technologies are aimed at improving the quality of customer service. In the current circumstances, special attention should be paid to measures that are focused on ensuring the safety of tourists.